anonymous
  • anonymous
f(x) = -2x-1 and h(x) = 3/x+1 what does (h*f)(2) = ??
Mathematics
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

Hero
  • Hero
f(x) = -2x-1 h(x) = 3/(x+1) f(2) = -2(2) - 1 = -4 - 1 = -5 h(2) = 3/(2+1) = 3/3 = 1 (h*f)(2) = h(2)*f(2) = 1*-5 = -5
Mertsj
  • Mertsj
f(2)=-5 h(2)=1 f(2)*h(2)=-5(1)=-5
anonymous
  • anonymous
Is that a valid way of writing f(2)*h(2) ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Hero
  • Hero
* means times. It's valid for when you're using a computer or a calculator
anonymous
  • anonymous
I meant (h*f) seems like multiplying "functions" rather than their values. Do you understand what I mean?
Hero
  • Hero
Yes, you can also multiply the functions, but that would take longer. It's easier to evaluate f(2) and h(2) then multiply that together. Either way, you would get the same answer.
anonymous
  • anonymous
Thank you
anonymous
  • anonymous
hmmmm......i got the answer -3/4 ?? that is the answer in the book i am using.
anonymous
  • anonymous
depends on whether you want \[f\times g(x)\] or \[f\circ g(x)\] they are different
anonymous
  • anonymous
ok that makes sense b/c the question was (h o f)(2)
anonymous
  • anonymous
then \[h\circ f(2)=h(f(2))=h(-5)=\frac{3}{-5+1}=-\frac{3}{4}\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.